The efficacy of psychodynamic psychotherapy for young adults: a systematic review and meta-analysis - Trotta, Antonella; Gerber, Andrew J.; Rost, Felicitas; Robertson, Sarah; Shmueli, Avi; Perelberg, Rosine J. (Frontiers in Psychology, 2024)
Objective One in six young adults presents with at least one mental health problem. However, so far, little attention has been directed to the mental health needs and the efficacy of therapeutic interventions for young adults. We conducted a systematic review and meta-analysis of the type, quality and efficacy of psychoanalytic psychotherapy for young people. Method We searched the PsycInfo, PubMed, Embase, and Cochrane databases to identify all the published randomized controlled trials (RCT), and naturalistic and observational studies of psychodynamic or psychoanalytic psychotherapies. We calculated the standardized mean difference in scores of psychodynamic interventions versus control conditions, adopting a random effects model (Hedges’ g). Results We identified 22 eligible studies, including 14 RCTs, and 8 naturalistic studies. Statistical analyses showed no significant difference between psychodynamic psychotherapy and other comparison treatments (psychotherapy or pharmacological interventions) for young adults (Hedges’g − 0.34 [95% CI: −0.991;-0.309], p = 0.304). Nevertheless, there was a significant effect of psychodynamic psychotherapy when compared with control conditions (waiting list or treatment as usual) for target symptoms (Hedges’g − 1.24 [95% CI: −1.97;-0.51], p < 0.001). Conclusion Our systematic review highlights important clinical implications in identifying the efficacy of psychoanalytic interventions for specific at-risk groups and suggests developing prevention strategies for mental health problems in young adulthood across cultures and context.